A Collection of Surveys on Market Experiments 2013
DOI: 10.1002/9781118790700.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Labor Markets and Policy Considerations: Incomplete Contracts and Macroeconomic Aspects

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Yet, starting with the seminal study by Fehr et al (1993), it has been shown that, typically, employers pay higher than minimum wages, employees choose higher than minimum effort and there is a significant positive relationship between wages offered and efforts chosen. Numerous replications of this experiment have shown the robustness of these results in many different circumstances (see Charness andKuhn, 2011, andCasoria andRiedl, 2013, for surveys of the literature on gift-exchange experiments).…”
Section: Hidden Action Problemsmentioning
confidence: 72%
“…Yet, starting with the seminal study by Fehr et al (1993), it has been shown that, typically, employers pay higher than minimum wages, employees choose higher than minimum effort and there is a significant positive relationship between wages offered and efforts chosen. Numerous replications of this experiment have shown the robustness of these results in many different circumstances (see Charness andKuhn, 2011, andCasoria andRiedl, 2013, for surveys of the literature on gift-exchange experiments).…”
Section: Hidden Action Problemsmentioning
confidence: 72%
“…Firms may be able to do so by explicitly setting a reference point in the incentive scheme (Christ et al, 2012;De Quidt, 2018;Fryer et al, 2012;Lazear, 1991;Luft, 1994) or by affecting the social norm that surrounds them (Akerlof, 1982;Aron, 1990;Aron and Olivella, 1994;Rey-Biel, 2008;Sliwka, 2007). If, for example, most workers obtain a yearly bonus, the normal payment in the firm is the base wage plus the bonus and, thus, earning only the base wage may be perceived as a punishment (Bowles and Polania-Reyes, 2012;Casoria and Riedl, 2013;Sobel, 2005).…”
Section: Organisational Punishment and Individual Preferences And Choicesmentioning
confidence: 99%
“…Models of wages as gift exchange suggest that workers are affected by moral sentiments and reciprocal behaviour when they choose the level of effort in the workplace. Workers react to firms giving high compensation and freedom by exerting high effort, but they respond negatively to rigid monetary schemes (Bolton and Dewatripont, 2005;Casoria and Riedl, 2013;Fehr and Schmidt, 1999;Fehr et al, 2009;Sliwka, 2007;Sobel, 2005). However, in echoing the insights of motivation theory, there is a recognition, in the labour economics literature, that punishment and rewards may have different effects on workers' moral feelings (Fehr and Gächter, 2002a;Gächter et al, 2009), with punishment having a larger negative effect than rewards (Rey-Biel, 2008).…”
Section: 'Deus Ex Machina': 2 Punishment Employee Motivation and Productivitymentioning
confidence: 99%
“…These findings have spawned a large literature (e.g.,, Fehr et al, 1996Fehr et al, , 1997Fehr et al, , 1998aFehr and Falk, 1999;Gächter and Falk, 2002;Hannan et al, 2002;Brandts and Charness, 2004;Brown et al, 2004;Charness, 2004). See Fehr et al (2009), Charness and Kuhn (2011), Casoria andRiedl (2013), andCooper andKagel (2016) for surveys.…”
Section: Introductionmentioning
confidence: 99%